1998
DOI: 10.1097/00005537-199801000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Osteologic Classification of the Sphenopalatine Foramen

Abstract: Textbook descriptions and illustrations of the opening of the sphenopalatine foramen (SPF) into the nasal cavity place it above and behind the posterior end of the middle turbinate (i.e., within the superior meatus). Although true for some skulls, this is not the situation for the majority and may be of importance, because the major blood supply to the nasal cavity enters via this route. Having studied 238 lateral nasal walls, the authors propose a classification of the osteology of the sphenopalatine foramen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 5 publications
9
42
2
2
Order By: Relevance
“…Based on these numbers, recently published papers [10][11][12] have suggested that there may be anatomical variants in the entrance point of the nasal arterial vessels (the branching pattern of the sphenopalatine artery, which in 95% of cases divides close to the sphenopalatine foramen, in the pterygopalatine fossa 10 ); this may depend on the number of foramens, and may be the cause of failure in the treatment of severe epistaxis or failure in arterial ligature. 4,12,13 According to some authors, the sphenopalatine foramen may be found in the superior nasal meatus in the nasal cavity. 6,14 However, if its position on the lateral nasal wall is established by the relation with the ethmoidal crest of the palatine bone, onto which it joins the posterior portion of the middle nasal turbinate, other studies locate it in the middle and/or superior nasal meatuses; 9,13 it is used as an anatomical landmark in endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these numbers, recently published papers [10][11][12] have suggested that there may be anatomical variants in the entrance point of the nasal arterial vessels (the branching pattern of the sphenopalatine artery, which in 95% of cases divides close to the sphenopalatine foramen, in the pterygopalatine fossa 10 ); this may depend on the number of foramens, and may be the cause of failure in the treatment of severe epistaxis or failure in arterial ligature. 4,12,13 According to some authors, the sphenopalatine foramen may be found in the superior nasal meatus in the nasal cavity. 6,14 However, if its position on the lateral nasal wall is established by the relation with the ethmoidal crest of the palatine bone, onto which it joins the posterior portion of the middle nasal turbinate, other studies locate it in the middle and/or superior nasal meatuses; 9,13 it is used as an anatomical landmark in endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4,12,13 According to some authors, the sphenopalatine foramen may be found in the superior nasal meatus in the nasal cavity. 6,14 However, if its position on the lateral nasal wall is established by the relation with the ethmoidal crest of the palatine bone, onto which it joins the posterior portion of the middle nasal turbinate, other studies locate it in the middle and/or superior nasal meatuses; 9,13 it is used as an anatomical landmark in endoscopic surgery. 15 It is essential that surgeons possess ample knowledge of the anatomy, physiology, surgical techniques and complications, 16 among other requirements, to undertake arterial ligature and other endoscopic procedures in the nasal cavity and avoid possible failures.…”
Section: Introductionmentioning
confidence: 99%
“…Epistaxis is classified clinically into anterior and posterior, and 90-95% of those are on the anterior region and most of them are on the little region, reveals in Kiesselbach plexus [1,2]. Sphenopalatine artery is responsible for most of the posterior epistaxis [3]. Bleeding caused by local traumas rather than anterior, whereas bleeding caused by systemic diseases usually generate from the posterior [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Sphenopalatine artery is responsible for most of the posterior epistaxis [3]. Bleeding caused by local traumas rather than anterior, whereas bleeding caused by systemic diseases usually generate from the posterior [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Quando duas ramificações arteriais estão presentes na cavidade nasal, a artéria nasal posterior lateral está situada mais anterior e inferior no forame (Wareing et al, 1998;Bolger et al, 1999 Figura 33. Parede lateral da cavidade esquerda do nariz.…”
Section: Predição Da Presença De Forame Acessório Através Da Avaliaçãunclassified